Examining Predictors of Environmental Health Knowledge and Competences in a Sample of Catalan Paediatricians - Mikel Subiza‐Pérez; Ferran Campillo i López; Kalliopi Vrostsou; Jesús Ibarluzea (Health Science Reports)
ABSTRACT Background and Aims Their close contact with the cokes paediatricians a key group of healthcare professionals for the dissemination of environmental health (EH) notions and the protection of children and families. However, international studies show that their knowledge and competences in EH matters are limited. Methods We recruited a sample of 293 paediatricians (80% women, mean age 47 years) working in Catalonia (Spain). The participants filled in a battery of questions that allowed us to describe EH knowledge and competences and study the role of certain potential predictors on these two EH constructs. Results We found that nature relatedness predicted both EH knowledge and competences. Those interested in environmental issues scored higher in EH knowledge, while older participants reported higher competence levels. We could not confirm the predictive role of other sociodemographic (e.g., gender) or psycho‐environmental variables (e.g., worry about environmental concerns). Conclusion Our results underscore the need to focus on training younger professionals and suggest that fostering psychological connections with nature and the environment might be a suitable approach.